Optimasi peningkatan asam gamma-aminobutirat (gaba) susu fermentasi kacang gude (Cajanus cajan (L) Mill.sp) menggunakan probiotik Lactiplantibacillus plantarum Dad-13 sebagai minuman kesehatan - Suryani, Ni Luh; Nursini, Ni Wayan; Wita Kusumawati, I Gusti Ayu; Agung Yogeswara, Ida Bagus (Jurnal SAGO Gizi dan Kesehatan, 2024)
Background: Pigeon pea (Cajanus cajan) is a type of legumes that is underutilized and not widely consumed. The utilization of pigeon pea as GABA-fermented drink have not yet been conducted. The Enhancement of GABA in pigeon pea is carried out by probiotic Lactiplantibacillus plantarum Dad-13. The enhancement of GABA in fermented pigeon pea drink will improve their functional effect and economic value.Objectives:  the aim of this study was to enhanced GABA content in fermented pigeon pea drink with various concentration of monosodium glutamate (MSG) using probiotic Lactiplantibacillus plantarum Dad-13.Methods: Randomized complete design was carried out in this study using experimental analysis. GABA content was determined using UPLC, total LAB was determined using spread plate method. Titration method was performed to determine the acidity and pH meter to determine the pH. Antioxidant capacity was determined using DPPH methodResults: The study showed a significant increase in GABA production, with the highest concentration reaching 92.07 mg/L in the treatment with 0.75% MSG. Additionally, there was an increase in the total count of lactic acid bacteria, total acidity, and antioxidant capacity, indicating an improvement in the physicochemical quality of the product. Organoleptic evaluation revealed panelists' preference for products with the addition of 0.25% and 0.75% MSG for taste, and 0% for texture.Conclusion: Fermentation of pigeon pea milk with the addition of Lactiplantibacillus plantarum Dad 13 and MSG successfully increased GABA production significantly, while also improving several aspects of the physicochemical and sensory quality of the product. These findings have important implications for the development of fermented pigeon pea milk as a new functional product enriched with GABA.